2003
DOI: 10.1016/s0167-2738(02)00841-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical characterisation of 3Y-TZP–Fe2O3 composites

Abstract: The influence of the addition of ferric oxide to 3Y-TZP on the conductivity and microstructure of sintered Y-stabilised tetragonal zirconia ceramics (3Y-TZP) was investigated. A comparison was made between two different dense 3Y-TZP -aFe 2 O 3 composites. Compacts were made by pressureless sintering at 1150 jC or by sinterforging at 1000 jC and 100 MPa. The sinterforging process resulted in smaller zirconia and hematite grains and a higher monoclinic zirconia content as compared to the compact that was sintere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…These observations can be explained by the incorporation of Fe 3+ cations in the zirconia structure, substituting Zr 4+ cations. It has been reported that the incorporation of Fe 3+ in the ZrO 2 lattice stabilizes the metastable t-ZrO 2 phase. , It should be noted that the mutual cationic solubility in the Fe–O–Zr system is very low, with an equilibrium solubility of Fe 2 O 3 in ZrO 2 of 2 mol % and ZrO 2 in Fe 2 O 3 of 1 mol % at 1373 K …”
Section: Resultsmentioning
confidence: 99%
“…These observations can be explained by the incorporation of Fe 3+ cations in the zirconia structure, substituting Zr 4+ cations. It has been reported that the incorporation of Fe 3+ in the ZrO 2 lattice stabilizes the metastable t-ZrO 2 phase. , It should be noted that the mutual cationic solubility in the Fe–O–Zr system is very low, with an equilibrium solubility of Fe 2 O 3 in ZrO 2 of 2 mol % and ZrO 2 in Fe 2 O 3 of 1 mol % at 1373 K …”
Section: Resultsmentioning
confidence: 99%
“…Workers have generally shown that when YSZ is implanted or alloyed homogeneously with Fe or Mn, its electrical conductivity is not significantly enhanced, even under moderately reducing conditions. 82,243,[284][285][286] Second, in isotope studies of lowtemperature bifunctional CO oxidation catalysts, such as Au/Fe 2 O 3 , workers have shown that the role of the transition metal in the support is essentially catalytic, i.e., stabilization of physisorbed O 2 at the Au/oxide interface, leading to enhanced oxidation rates. [287][288][289] It is likewise possible that enhanced performance of metal cathodes on YSZ incorporating transition metals or (other d-orbital cations) is an electrochemical-kinetic effect localized to the TPB where by "localized" we mean simply "within a distance accessible by electrons from the electrode material".…”
Section: Alteration Of Materials Properties Near the Interfacementioning
confidence: 99%
“…First, it should be emphasized that a finite rate of oxygen exchange at the electrolyte surface (as measured at equilibrium by isotope methods) is a necessary but insufficient criterion for finite rates of oxygen reduction; for there to be a net production of O 2- at the electrolyte surface, electrons must also be able to gain access to the surface. Workers have generally shown that when YSZ is implanted or alloyed homogeneously with Fe or Mn, its electrical conductivity is not significantly enhanced, even under moderately reducing conditions. ,, Second, in isotope studies of low-temperature bifunctional CO oxidation catalysts, such as Au/Fe 2 O 3 , workers have shown that the role of the transition metal in the support is essentially catalytic , i.e., stabilization of physisorbed O 2 at the Au/oxide interface, leading to enhanced oxidation rates. It is likewise possible that enhanced performance of metal cathodes on YSZ incorporating transition metals or (other d-orbital cations) is an electrochemical−kinetic effect localized to the TPB where by “localized” we mean simply “within a distance accessible by electrons from the electrode material”. Indeed, as shown in Figure , the enhancements observed by van Hassel and co-workers upon implantation of Fe into YSZ correspond to an increase in the apparent exchange current density while the Tafel slope remains constant over several orders of magnitude.…”
Section: 2 Alteration Of Materials Properties Near the Interfacementioning
confidence: 99%
“…Under these conditions, the conductivity is predominantly ionic. When the content of Fe-based impurities exceeds the solubility limit at around 6% mol (2.84%wt), paths of hematite have been reported to generate across the sample (Verkerk et al, 1982;Kharton, 1999;Boukamp, 2003). Setup for the characterization of a cryogenic RP-WELL at 90 K (vapor pressure 1.2 bar).…”
Section: Discussionmentioning
confidence: 99%
“…In this case the dopant acts as an electron donor, up to concentrations of 10% Zr atoms per Fe atom (or 16.3%wt, in weight percentage), when a new phase is formed. For larger concentrations, ZrO 2 (zirconia) might be used instead, leading to speculation of additional contributions to Frontiers in Detector Science and Technology frontiersin.org the electron conductivity, either through the grain-boundary (Boukamp, 2003), or electron hopping through Fe cations in the zirconia lattice (Kharton, 1999). Given this landscape, a natural possibility was to evaluate ceramics based on Fe 2 O 3 and zirconia stabilized with yttria at 8% molar (hereafter yttria-stabilized zirconia, YSZ) for which a large body of experience exists ( (Verkerk et al, 1982;Slilaty, 1996;Gao et al, 2008;Molin et al, 2009;Bohnke et al, 2014;Guo, 2021) and references therein).…”
Section: Open Access Edited Bymentioning
confidence: 99%